2011
DOI: 10.1007/s00436-011-2588-9
|View full text |Cite
|
Sign up to set email alerts
|

Description of Sarcocystis anasi sp. nov. and Sarcocystis albifronsi sp. nov. in birds of the order Anseriformes

Abstract: On the basis of the already published morphological, 18S rDNA, 28S rDNA data (Kutkienė et al., Parasitol Res 99:562-565, 2006; Parasitol Res 102:691-696, 2008; Parasitol Res 104:329-336, 2009), and ITS-1 region investigation results of sarcocysts presented in this paper, Sarcocystis albifronsi sp. nov. from the white-fronted goose (Anser albifrons) and Sarcocystis anasi sp. nov. from the mallard duck (Anas platyrhynchos) are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…3; Dahlgren et al, 2007) and the other with species of Sarcocystis that use avian intermediate hosts (Lineage 1; Fig. 3; Kutkiené et al, 2012). Samples that grouped in Lineage 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3; Dahlgren et al, 2007) and the other with species of Sarcocystis that use avian intermediate hosts (Lineage 1; Fig. 3; Kutkiené et al, 2012). Samples that grouped in Lineage 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results support at least two separate lineages of Sarcocystis . Samples that grouped in Lineage 1 were genetically similar to S. albifronsi (GenBank Accession no: EU502868) and S. anasi (GenBank Accession no: EU553477), which Kutkiené et al (2012) isolated from tissue of greater white-fronted geese ( Anser albifrons ) and mallard ducks ( Anas platyrhynchos ), respectively. Samples in Lineage 2; were related to Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…have been detected in psittacines either with no clinical signs or with nonspecific signs, suggesting that seroconversion did not represent an active infection in these birds but might be related to exposure to the parasite or subclinical infections (CRAY et al, 2005). Diagnosis of sarcosporidiosis is usually performed by post-mortem examinations (KUTKIENĖ et al, 2010(KUTKIENĖ et al, , 2012PRAKAS et al, 2014), and ante mortem examinations are performed by muscle biopsies (CRAY et al, 2005), being therefore underdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcocystis in birds. To date, 30 named Sarcocystis species forming sarcocysts in the muscle tissues of birds belonging to at least 13 avian orders are known (Kutkienė et al, 2012). Two Sarco-cystis species were described in chickens, S. wenzeli, whose definitive hosts are dogs or cats, and S. horvathi, whose definitive host is still undiscovered (Odening, 1997).…”
Section: Investigations Of Wild Animalmentioning
confidence: 99%
“…On the basis of the results of the cyst wall ultrastructure and DNA analysis, using 18� rRNA gene, 28� rRNA gene and IT�-1 region genetic markers, three new Sarcocystis species from Anseriformes were described: S. wobeseri parasitizing the barnacle goose (Branta leucopsis) and mallard, S. anasi from the mallard, and S. albifronsi from the white-fronted goose (Butkauskas et al, 2007;Kutkienė et al, 2006Kutkienė et al, , 2008Kutkienė et al, , 2010Kutkienė et al, , 2012. Experimentally it was showed that the arctic fox (Alopex lagopus) is one of definitive hosts of S. albifronsi (Kutkienė et al, 2006).…”
Section: Investigations Of Wild Animalmentioning
confidence: 99%